Fifth Five - Year Plan A Draft Outline Government of Himachal Pradesh - Planning Commission (Planning Commission)
During 1966-67 certain areas of erstwhile Punjab were merged with this Pradesh. As such a new series of State Domestic Product was developed for the years 1966-67 onwards. According to these estimates the trend growth rate of economy of present Himachal Pradesh was 3.3. per cent per annum during the period 1967-68 to 1969-70. In terms of per capita income, this rate was only 1.3 percent per annum.
Government of Himachal Pradesh, Planning Department